Lymphomatoid contact dermatitis associated with textile dye at an unusual location - Tuğba Kevser Uzunçakmak; Necmettin Akdeniz; Seyma Özkanlı; Zafer Türkoğlu; Ebru Itır Zemheri; Ayşe Serap Karadağ (Wolters Kluwer Medknow Publications, 2015)
Lymphomatoid contact dermatitis (LCD) is a rare variant of noneczematous allergic contact dermatitis, which can mimick parapsoriasis or early-stage mycosis fungoides with its atypical clinical and histopathological manifestation. Many different haptens have been reported to be associated with this reaction. Histopathological examination, immunhistochemistry, clonality tests, and patch tests are mandatory for diagnosis and differential diagnosis. We present a 48-year-old male with a four years history of a relapsing erythematous plaque on the glans penis. Topical corticosteroids had been prescribed but he complained of relapse upon withdrawal. Histopathological examination was consistent with LCD. Thin layer rapid use epicutaneous patch test result was (++) for disperse blue and nickel sulfate. We present this case because of its rarity and unusual localization. This kind of allergic contact dermatitis should be remembered in differential diagnosis of nonspesific pruritic plaques over the genital region.